Legal Regulation of Agricultural Taxation - Kovalchuk, Inna; Melnyk, Victoria; Novak, Tamara; Pakhomova, Anna (European Journal of Sustainable Development, 2021)
The tendencies of development and peculiarities of agribusiness enterprises activity are established within this research framework. Globalization and liberalization processes have spread rapidly over the past two decades, attracting more and more countries and linking their economies to the world economy. The agro-industrial sector of the economy deserves special attention in international cooperation, characterized by a particular feature, linking geopolitical, economic, social, environmental, sanitary, hygienic norms and rules. Therefore, the experience gained by countries that have long been members of the WTO and have passed certain stages of development and regulation of the tax policy of agribusiness enterprises is worth studying, analyzing, and implementing. The comparative analysis of the results of the realization of the state policy in the field of taxation of agribusiness is carried out during recent years. This research paper analyzes the generalized experience of economically developed countries in the formation of tax policy in the field of agribusiness regulation and identifies opportunities for its application in Ukraine. The study results determine the practical significance of the article, which is determined by the possibility of using the proposed mechanisms to improve the tax policy in the field of agribusiness regulation and identify opportunities for its application in Ukraine.